2018
DOI: 10.1128/msphere.00205-18
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile Lipoprotein GerS Is Required for Cortex Modification and Thus Spore Germination

Abstract: The Gram-positive, spore-forming bacterium Clostridium difficile is a leading cause of antibiotic-associated diarrhea. Because C. difficile is an obligate anaerobe, its aerotolerant spores are essential for transmitting disease, and their germination into toxin-producing cells is necessary for causing disease. Spore germination requires the removal of the cortex, a thick layer of modified peptidoglycan that maintains spore dormancy. Cortex degradation is mediated by the SleC hydrolase, which is thought to reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 65 publications
(132 reference statements)
7
66
0
Order By: Relevance
“…Our results support the first model whereby CspB, CspA, and CspC are in a germinosome complex – similar to the germinosome complex found in B. subtilis [53]. Recent studies on GerS have shown that GerS likely does not form a complex with other germination proteins [52, 54]. Rather, it is required to generate cortex-specific modifications in the spore and thus, important for germination of the spore because the SleC cortex lytic enzyme depends on cortex-specific modifications to degrade the cortex layer efficiently [54].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results support the first model whereby CspB, CspA, and CspC are in a germinosome complex – similar to the germinosome complex found in B. subtilis [53]. Recent studies on GerS have shown that GerS likely does not form a complex with other germination proteins [52, 54]. Rather, it is required to generate cortex-specific modifications in the spore and thus, important for germination of the spore because the SleC cortex lytic enzyme depends on cortex-specific modifications to degrade the cortex layer efficiently [54].…”
Section: Discussionsupporting
confidence: 85%
“…Recent studies on GerS have shown that GerS likely does not form a complex with other germination proteins [52, 54]. Rather, it is required to generate cortex-specific modifications in the spore and thus, important for germination of the spore because the SleC cortex lytic enzyme depends on cortex-specific modifications to degrade the cortex layer efficiently [54]. Based upon prior work from our lab, proSleC is unlikely to be part of this complex because SleC is three to four times more abundant than CspB or CspC, depending upon the strain analyzed [33].…”
Section: Discussionmentioning
confidence: 99%
“…Sporulation was induced in 70:30 agar plates for 2 to 3 days as previously described ( 25 , 53 ). C. difficile sporulating cells were washed 5 to 6 times in ice-cold water, incubated overnight at 4°C, and treated with DNase I (New England BioLabs) at 37°C for 60 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…In group of rod shape bacteria producing endospores, Lpp genes are also involved in the spore germination process for example GerA/D in Bacillus subtilis or GerS in Clostridium difficile (Pelczar and Setlow, 2008;Li et al, 2014;Diaz et al, 2018). In fact, a Bacillus anthracis lgt mutant lacking the lipid moiety germinated inefficiently; in line, the spore displayed attenuated virulence in the mouse infection model (Okugawa et al, 2012).…”
Section: Spore Germinationmentioning
confidence: 99%